Kajian Teknis Produktivitas Alat Gali Muat Dan Alat Angkut Dalam Upaya Pencapaian Target Produksi Bijih Nikel Pada Mitra Kerja PT Manado Karya Anugrah Di PT Gag Nikel Raja Ampat Papua Barat: kajian teknis alat gali muat dan alat angkut - PAUSPAUS, Lutfiah Izzani; Sidiq, Hidayatullah; Mukarrom, Faisol (ReTII, 2022)
PT Gag Nickel is a subsidiary of PT Aneka Tambang Tbk. which is engaged in the mining of laterite nickel ore and is located on Gag Island, District of West Waigeo Islands, Raja Ampat Regency, West Papua Province. The mining method applied in mining laterite nickel ore is the open cast method. PT Manado Karya Anugrah is one of PT Gag Nickel’s partners which has been operating since June 2021 and has a production target of 75,000 wmt/month. Nickel ore mining is carried out using a Caterpillar 330GC excavator and an Volvo A40G Articulated Dump Truck. The average mining front-stockyard distance is 2,120 meters. In 2021, PT Manado Karya Anugrah’s ore production target of 75,000 wmt/month has not been achieved. Several factors that affect the failure to achieve production targets are the condition of the mining front which is often damaged, the condition of the hauling road that needs maintenance, and wasted working time due to work obstacles, both avoidable and unavoidable obstacles. These obstacles reduce the working time of the tool causing the Use Of Availability to be low. Efforts to increase production are carried out by improving the loading point floor, changing loading patterns, maintaining haul roads to minimize tool cycle time, increasing equipment performance, increasing available time from 11 hours/shift to 12 hours/shift, and optimizing match factor.